Proyecto para la creación de una hostería en la comuna San pablo en la provincia de Santa Elena, ruta del spondylus - Alvarado Guanga, Adela A. (2009)
San Pablo commune currently owns an unmet demand for housing, because every week this place is visited by tens of upper-middle-class tourists who usually stay in other populations. The construction of a hostel in this community is based on the demand of tourists looking for accommodation. The resource investment kicking off the first phase of the project (that aspect will be addressed in the development of it), are fully accessible. There is a spot of 506 m2, located at the foot of the road overlooking the sea, which will be seventy percent financing through a bank loan to the CFN (Corporación Financiera Nacional), thirty percent own equity remaining path and thus to begin its construction. This investment project shows that there is a market exists and the resources necessary to carry out the same, and it sought to harness and rescue this tourist area, offering high quality services in both the design and construction of facilities and the operation of tourism-oriented services to foreign and domestic tourism.